Aspek Distribusi pada Ketahanan Pangan Masyarakat di Kabupaten Tapin - Emy Rahmawati (AGRIDES: Jurnal Agribisnis Perdesaan, 2012)
The objectives of the research were to find out the distribution channels of the staple food, namely the commodity of rice, and to analyze the cost, margin, and income from each marketing agent related to the rice distribution in Tapin Regency. The data were collected by conducting direct interviews with the players or the marketing agents getting involved in the food distribution. There were six distribution channels of rice, in which the role of LUEP was notably dominant. The biggest margin occurred between wholesalers and local retailers. Likewise, the biggest income was received by local retailers.